Phenotypic variability for different traits of oat panicle (Avena sativa L.) - Federizzi, Luiz Carlos; Acauan, Laurenço Rolim; de Carvalho, Fernando Irajá Felix; Bodanese-Zanettini, Maria Helena (Pesquisa Agropecuaria Brasileira, 1995)
To determine the phenotypic variability for traits of oat panicle among the varieties grown in the southern Brazil, with and without application of fungicide. The experiment was done at the Experiment Station of UFRGS, in Eldorado do Sul, Brazil. Each plot had four lines of 5m of length, spaced 0,20m, with three replications without fungicide, and three replications with apllication of propiconazole 0,5 l/ha. Five panicles per plot where collected before harvest and panicle weight, number of flowers/panicle, number of grains/panicle, fertility, and grain weight, were determined. Grain yield was obtained by harvesting two central rows of each plot. Great phenotypic variability was observed for all traits with and without fungicide application. Varieties with higher grain yield revelated different values for the traits analised. These results indicate that different combinations of traits may produce high grain yield and different oat plant ideotype can be adequate for the environments of the southern Brazil.